The marketisation of higher education: symptoms, controversies, trends - Hanna Hall (Ekonomia i Prawo, 2018)
Motivation: Marketisation of higher education accompanying the development of a market economy having expressed, among others, the ‘imitation’ of management models specific to the enterprise sector, an adaptation of the market terminology, changing roles of students and the importance of their satisfaction with the study causes still a lot of controversy in the academic community, dividing it into supporters and opponents of the current process with a strong predominance of the first group. Aim: The aim of this article is to present the arguments and opinions of supporters and opponents (deck research) and the chosen Polish university representatives (primary research) of the marketization process of higher education. In the article the results of desk research as well as the author’s own research will be used. Results: Supporters of marketisation argue that this process will turn universities into more flexible, more efficient and more responsive to the needs of society, the economy, students and parents institutions. Opponents pay attention to the cultural, intellectual and pedagogic consequences of this process. Both groups conclude that there is no turning back from this process and it cannot be avoided. Intensification of university marketing is perceived both by representatives of Polish public and non-public universities, as shown by the research conducted by the author. There were no significant differences in terms of the statements made by representatives of the different types of universities. Only sometimes more decision-making flexibility of non-public universities was emphasized, better use of information technology in their communication with prospective and current students, better knowledge of IT tools as well as slightly more intensification of promotional activities.